2022
DOI: 10.3390/plants11141861
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Comprehensive in Silico Characterisation of a New 3-Hydroxy-3-Methylglutaryl-Coenzyme A Reductase 4 (HMGR4) Gene Promoter from Salvia miltiorrhiza: Comparative Analyses of Plant HMGR Promoters

Abstract: Salvia miltiorrhiza synthesises tanshinones with multidirectional therapeutic effects. These compounds have a complex biosynthetic pathway, whose first rate limiting enzyme is 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGR). In the present study, a new 1646 bp fragment of the S. miltiorrhiza HMGR4 gene consisting of a promoter, 5′ untranslated region and part of a coding sequence was isolated and characterised in silico using bioinformatics tools. The results indicate the presence of a TATA box, tandem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Using Arabidopsis thaliana HMGR (ID: 7ULI in RCSB PDB) and Medicago sativa CHS (ID: 1I86 in RCSB PDB) as templates, the tertiary structures of PtHMGR and PtCHS were modeled by SWISS-MODEL software. The results (Figs [22][23][24] showed that the main structures of PtHMGR and PtCHS were α-helices, β-turns, and random-coils, and the directions from the N-terminus to the C-terminus are shown in red, orange, yellow, green, cyan, blue, and purple, respectively. 390 amino acids of PtHMGR were highly similarity with to template 7ULI, which had a coverage rate of 92.0%.…”
Section: Secondary and Tertiary Structure Of Pthmgr And Ptchsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Arabidopsis thaliana HMGR (ID: 7ULI in RCSB PDB) and Medicago sativa CHS (ID: 1I86 in RCSB PDB) as templates, the tertiary structures of PtHMGR and PtCHS were modeled by SWISS-MODEL software. The results (Figs [22][23][24] showed that the main structures of PtHMGR and PtCHS were α-helices, β-turns, and random-coils, and the directions from the N-terminus to the C-terminus are shown in red, orange, yellow, green, cyan, blue, and purple, respectively. 390 amino acids of PtHMGR were highly similarity with to template 7ULI, which had a coverage rate of 92.0%.…”
Section: Secondary and Tertiary Structure Of Pthmgr And Ptchsmentioning
confidence: 99%
“…Its expression level affects the accumulation of saponins in P. tenuifolia. To date, the HMGR genes in many plants have been successfully isolated and cloned, such as Alisma orientale [18], Bunium persicum [19], Cucumis melo [20], Lithospermum erythrorhizon [21], Catharanthus roseus [22], Salvia miltiorrhiza [23] and etc. However, the involvement of HMGR in the terpenoid biosynthetic pathway has not yet been identified in P. tenuifolia.…”
Section: Introductionmentioning
confidence: 99%